Physics-guided bidirectional synergistic fusion network for stern bearing fault diagnosis in ship propulsion systems - Hongdi Zhou; Yong Pan; Tielin Shi; Jian Duan; Chao Qian; Guoping Yan; Yijie Cai (Ocean Engineering, 2026)

Head-to-head comparison of plasma biomarker assays across platforms for amyloid pathology in a multicenter cohort - Xinyi Lv; Kaiyuan Shen; Qianhua Zhao; Guoping Peng; Huayan Liu; Feng Gao; Xiaodong Pan; Wei Chen; Peilin Lu; Haining Zhang; Shuting Zhang; Mengya Xing; et al. (Science Bulletin, 2026)

Decolorization of Antarctic krill hydrolysate for salt reduction in surimi gel: improvement of taste, gel properties, and flavor profile - Yurui Zhang; Bo Wang; Yan Li; Xin Jiang; Shangkun Li; Keqiang Lai; Guoping Zhu; Wenzheng Shi (Food Research International, 2026)

Magnetic extraction of highly polar pesticides: Method optimization and mechanism - Zhuangzhuang Shi; Huiling Shi; Ning An; Jinwang Li; Guoping Zhao; Xiaoxu Zhang; Xuefeng Yin (Food Chemistry, 2026)

Five daucane-type sesquiterpenes isolated from the roots of Ferula songarica Pall. ex Schult. and their anti-gastric cancer activity - Xiaotong Chang; Guoping Wang; Degang Qing; Yu Sun; Yaqin Zhao; Ning Lu; Leiling Shi; Jie Lv (Natural Product Research, 2026)

Combined aperture widening and strong polarization in Li+-exchanged mordenite for efficient direct air capture of CO2 - Zhifu Liu; Guanghui Shi; Shuzhuang Sun; Yong Wang; Jingyue Shang; Songbai Hu; Wenkang Deng; Chuhan Fu; Chenghao Liu; Xiao Wang; Tao Qi; Guoping Hu (Chemical Engineering Journal, 2026)

Permafrost peatland development at thermokarst lake margins in the northern Greater Khingan Mountains of Northeast China: Rapid areal increase and carbon accumulation since the 1950s - Jiangtao Gao; Jinxin Cong; Guangxin Li; Yingjie Shi; Dongxue Han; Guoping Wang; Chuanyu Gao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The first report of load and congener group profile of short-chain chlorinated paraffins (SCCPs) in mackerel icefish Champsocephalus gunnari and painted notie Nototheniops larseni at South Georgia, Antarctic during winter - Shi Qiu; Guoping Zhu (Environmental Research, 2025)

Advancements in function recognition of staphyloxanthin and targeted inhibitor development - Jiang Chang; Min Yue; Guoping Zhao; Biao Tang; Chunlei Shi (Current Opinion in Food Science, 2025)

Regulating and remolding of soil water flux by sparse shrubs in arid desert regions - Yunfei Chen; Xiuhua Liu; Yandong Ma; Ce Zheng; Yijian Zeng; Wande Gao; Junqi He; Lianyi Hao; Zuyu Liu; Changchun Shi; Guoping Zhao (CATENA, 2024)

Correction to: Estimation of evapotranspiration through an improved daily global solar radiation in SEBAL model: a case study of the middle Heihe River Basin - Jingqiu Yin; Xinfa Qiu; Shoubo Li; Guoping Shi; Huiyu Liu; Haixuan Zhou; Hanwei Wu (Theoretical and Applied Climatology, 2024)

Estimation of evapotranspiration through an improved daily global solar radiation in SEBAL model: a case study of the middle Heihe River Basin - Jingqiu Yin; Xinfa Qiu; Shoubo Li; Guoping Shi; Huiyu Liu; Haixuan Zhou; Hanwei Wu (Theoretical and Applied Climatology, 2024)

Constraint information extraction for 3D geological modelling using a span-based joint entity and relation extraction model - Can Zhuang; Chunhua Liu; Henghua Zhu; Yuhong Ma; Guoping Shi; Zhizheng Liu; Bohan Liu (Earth Science Informatics, 2024)

Evaluation of MACC total aerosol optical depth and its correction model based on the random forest regression - Yang Zhen; Guoping Shi (Theoretical and Applied Climatology, 2023)

Genomic insights into the genetic basis of cotton breeding in China - Yiqian Li; Zhanfeng Si; Guoping Wang; Zhuolin Shi; Jinwen Chen; Guoan Qi; Shangkun Jin; Zegang Han; Wenhao Gao; Yue Tian; Yun Mao; Lei Fang; et al. (Molecular Plant, 2023)

Electrode materials for Li/Na storage from mechanochemically synthesised MOFs/MXene Composites: A Solvent-free approach - Xiaoyan Shi; Weiquan Liang; Guoping Liu; Bin Chen; Lianyi Shao; Yanxue Wu; Zhipeng Sun; Felipe García (Chemical Engineering Journal, 2023)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A botanical medicine dragon’s blood exhibited clinical antithrombosis efficacy similar to low molecular weight heparin - Jiangbin Liang; Song Mei; Xiangyu Qiao; Wei Pan; Yan Zhao; Shaohui Shi; Yaling Zhai; Haizhao Wen; Guoping Wu; Chengyu Jiang (Science China Life Sciences, 2021)

Dominant factor of dry‐wet change in China since 1960s - Jinqin Xu; Dandan Wang; Xinfa Qiu; Yan Zeng; Xiaochen Zhu; Mengxi Li; Yongjian He; Guoping Shi (International Journal of Climatology, 2021)
The dry‐wet climate conditions of an area are mainly determined by the water input (e.g., precipitation, P) and output (e.g., potential evapotranspiration, PET). Based on three dry‐wet indices and the differential equation, this study designed a new attribution method to quantify the contributions of P and PET to the dry‐wet change, so as to determine the dominant factors of the dry‐wet change over whole China (CHINA) and various hydroclimate regions (i.e., arid region, AR; semi‐arid region, SAR; semi‐humid region, SHR; and humid region, HR) during 1960–2018 and six interdecadal periods. Results showed that the overall weak drying in CHINA was dominated by an increase in PET, while climate humidification in AR and HR was dominated by an increase in P, climate drying in SHR was dominated by the reduced P, and the weak drying in SAR was co‐dominated by P and PET during 1960–2018. The dominant factors of dry‐wet change over CHINA and each hydroclimate region varied in different decades. Briefly, climate humidification in CHINA and various hydroclimate regions was basically dominated by P in different decades, and the drying was mainly dominated by P in the 1960s–1980s, but the contribution of PET to climate drying began to become prominent after the 1980s. Besides, we found that P contributed more to dry‐wet change than PET on the station and regional scales, but the contribution of P to climate drying on a national scale was underestimated to some extent due to the regional offset effect of the increase/decrease in P during 1960–2018, as well as in the 1990s. These findings implied that the importance of research on the regional or local scale, and equal attention should be paid to the effects of P and PET changes in the future drought or dry‐wet change research.

Lasting days contributed most to the variation of ≥ 10 °C accumulated temperature from 1961 to 2010 in China - Jinqin Xu; Xinfa Qiu; Yan Zeng; Mengxi Li; Guoping Shi; Zhe Wang; Xiaochen Zhu; Dandan Wang (Theoretical and Applied Climatology, 2019)

Effects of Urban–rural Atmospheric Environment on Heavy Metal Accumulation and Resistance Characteristics of Pinus tabulaeformis in Northern China - Ruirui Zhao; Tong Yang; Cong Shi; Meili Zhou; Guoping Chen; Fuchen Shi (Bulletin of Environmental Contamination and Toxicology, 2019)

Comparison of two air temperature gridding methods over complex terrain in China - Guoping Shi; Zhian Sun; Xinfa Qiu; Yan Zeng; Peng Chen; Changjie Liu (Theoretical and Applied Climatology, 2018)

New method for estimating daily global solar radiation over sloped topography in China - Guoping Shi; Xinfa Qiu; Yan Zeng (Advances in Atmospheric Sciences, 2018)

Soil aggregate characteristics and stability of soil carbon stocks in a Pinus tabulaeformis plantation - Guoping Chen; Zhangying Gao; Lihong Zu; Lili Tang; Tong Yang; Xiaomei Feng; Tiejian Zhao; Fuchen Shi (New Forests, 2017)

Modification of the SUNFLUX solar radiation scheme with a new aerosol parameterization and its validation using observation network data - Yongjian He; Zhi’an Sun; Guoping Shi; Jingmiao Liu; Jiandong Li (Advances in Atmospheric Sciences, 2017)

The evolution of water property in the Mackenzie Bay polynya during Antarctic winter - Zhixin Xu; Guoping Gao; Jianping Xu; Maochong Shi (Journal of Ocean University of China, 2017)